ANALYSIS OF THE TRAFFIC IMPACT OF DEVELOPMENT SEKOLAH MARDI WALUYA KOTA BOGOR - Sudrajat, Adriyanto; Murtedjo, Tedy; Chayati, Nurul; Rulhendri, Rulhendri (ASTONJADRO, 2020)
The construction of a certain area will have an impact on the performance of the surrounding traffic, this is due to the new movements caused, one of which is the expansion of the Mardi Waluya School building located in the city of South Bogor, referring to the regulation of the minister of transportation no. 75 of 2015, then the activity must be carried out a Traffic Impact Analysis, this analysis is carried out to find out how much impact caused by the generation and attraction by the new activity center. With standard calculations based on the Indonesian Road Capacity Manual (MKJI 2017). From the analysis obtained, the average value of the Existing VCR on the Jalan Pahlawan section is 0.55, Jl. Dreded 0,17, Jl. Aut 0,68, Jl. R Saleh Bustaman 0.58, Jl. Empty 0.98. There was no significant effect on traffic performance during construction. But it is predicted that in the period 2021-2025 it will change with a VCR value of: Jl. Pahlawan 0.57 - 0.63 Jl. Dreded 0,18 - 0,20 Jl. Aut 0,69 - 0,77, Jl. R Saleh Bustaman 0.59 - 0.65, Jl. Empty 1.00 - 1.10. An impact handling simulation was conducted to improve traffic performance, indicated by the VCR value on the Jl. Pahlawan 0.53 - 0.58 Jl. Dreded 0,17 - 0,19 Jl. Aut 0,39 - 0,43, Jl. R Saleh Bustaman 0.54 - 0.60, Jl. Empty 0.76 - 0.84.